Odpowiedzi

2010-02-16T19:37:51+01:00
5(-2a+b)=-10a+5b
-4(5y-z)=-20y+4z
0,2(10x-y)*0,4=(2x-0,2y)0,4 = 0,8x-0,08y
(-0,5y+9)*0,8=-0,4y+7,2
(-2a+4b)*(-1,5b)=3ab-6b²
1/5(10x+2,5)-0,4 =(2x+½)-0,4 = -0,8x-0,2
1/3(3y-2,7)=y-27/30
-2/3(3,6a-1,5b)=-2i12/30a+1b
Najlepsza Odpowiedź!
2010-02-16T19:38:31+01:00
5(-2a+b)= -10a+5b
-4(5y-z)= -20y+4z
0,2(10x-y)*0,4=(2x-0,2y)*0.4=0,8x-0,08y
(-0,5y+9)*0,8= -0,4y+7,2
(-2a+4b)*(-1,5b)=3ab-6b²
1/5(10x+2,5)-0,4 =2x+0,5-0,4
1/3(3y-2,7)=y-0,9
-2/3(3,6a-1,5b)= -2,4a+1b
2010-02-16T19:38:47+01:00
1) 10a +5b
2) 20y + z
3) 2x-0,2y
4)4y+7,2
5)3ab-6b²
6)-0,8x-0,2
7)y-27/30

8)2i12/30a+1b